Synthesis gas production by combined reforming of CO2-containing natural gas with steam and partial oxidation in a multistage gliding arc discharge system - Pornmai K. (American Chemical Society, 2014)
In this research, the effect of multistage gliding arc discharge system on the process performance of combined natural gas reforming with steam and partial oxidation has been investigated. The simulated natural gas used in this study contains 70% methane, 5% ethane, 5% propane, and 20% carbon dioxide. An increase in stage number of gliding arc reactors from 1 to 3, at a constant feed flow rate, enhances all reactant conversions and H2 yield with a substantial reduction of energy consumption. However, at a given residence time, an increase in stage number from 1 to 3 shows no effect on any hydrocarbon reactant conversions or the selectivities for H2 and CO but has a drastic reduction of energy consumption. For either the constant feed flow rate or the constant residence time, 3 stages are found to be an optimum stage number of gliding arc reactors for synthesis gas production from the reforming of CO2-containing natural gas with steam and partial oxidation, in terms of the lowest specific energy consumptions, and highest CO2 conversion with reasonably high yields for both H2 and CO. © 2014 American Chemical Society.